2020
DOI: 10.3389/fendo.2020.561085
|View full text |Cite|
|
Sign up to set email alerts
|

Miscarriage Rate Is High With Frozen-Thawed Blastocysts Arising From Poor-Quality Cleavage Stage Embryos

Abstract: Embryos with low morphological scores can still develop to the blastocyst stage and result in good clinical outcomes. However, no studies have reported the possible effects of transferring cryopreserved blastocysts developed from poor-quality cleavage stage embryos on pregnancy and perinatal outcomes. In this retrospective study, the clinical value of transferring blastocysts derived from day 3 poor-quality cleavage stage embryos during in vitro fertilization and embryo transfer procedures was evaluated. Accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Our study suggested that morphologically good Day 5 blastocysts should be first considered for transfer, not only because of the high implantation potential, as a previous study reported (45), but also because of the low rate of pregnancy loss. Furthermore, our study may help to explain a recently published study indicating that FET cycles with blastocysts arising from poor-quality cleavage embryos showed a significantly higher miscarriage rate (46). As we showed in the present study, the rate of Day 5 blastocysts from grade III Day 3 embryos was 29%, while that from grade I embryos was 62.7%.…”
Section: Discussionsupporting
confidence: 85%
“…Our study suggested that morphologically good Day 5 blastocysts should be first considered for transfer, not only because of the high implantation potential, as a previous study reported (45), but also because of the low rate of pregnancy loss. Furthermore, our study may help to explain a recently published study indicating that FET cycles with blastocysts arising from poor-quality cleavage embryos showed a significantly higher miscarriage rate (46). As we showed in the present study, the rate of Day 5 blastocysts from grade III Day 3 embryos was 29%, while that from grade I embryos was 62.7%.…”
Section: Discussionsupporting
confidence: 85%
“…The results of Dozortsev et al ( 23 ) concluded that the fertilization rate of PESA from different sperm sources was significantly higher than that of TESA, but the clinical pregnancy rate was significantly lower and the miscarriage rate was higher than that of TESA. High-quality blastocysts are usually able to achieve higher pregnancy and implantation rates, which are important indicators of the developmental potential of transferred embryos in vivo ( 24 ). With regard to the effect of sperm from different surgical sources on pregnancy outcomes in assisted reproduction, some authors ( 25 , 26 ) have concluded that there is no significant difference in the effect of testicular and epididymal sperm on clinical pregnancy rates and miscarriage rates.…”
Section: Discussionmentioning
confidence: 99%
“…However, the culture system may lead to the risk of losing a part of the embryos, which may not survive the challenge of extended culture [ 20 ]. According to previous studies, the blastulation rate that originated from slow-growing embryos was between 20% and 50% [ 21 , 22 , 23 ], which may reflect the fact that at least one of the halves of the slow-growing embryos may fail to extend to blastocysts. On the one hand, the day-3 slow-growing embryos decrease the chances of achieving the blastocyst stage [ 24 ]; on the other hand, the culture system also plays an important role that may have a negative effect on embryos.…”
Section: Discussionmentioning
confidence: 99%